Popularizing Visuo-Spatial Training for Reading Challenges: A Call to Experts in Support of Language and Non-language-based Cognitive Skills Strengthening - Trebeau Crogman, Maryam; Crogman, Horace (Frontiers in Education, 2020)
We propose to researchers, educators and professionals a discussion which contributes to a growing body of research questioning how dyslexia and reading challenges have been researched, diagnosed and remedied. Also included is a discussion for educators and researchers including questioning the definitions of dyslexia, how educators could view dyslexia against mainstream opinions, the place of culture, language, and multisensory teaching. Two literature reviews and a pilot study are briefly described to provide the initial grounds and design to propose an alternative approach to growing our understanding and studying the connections between training non-language-based (NLB) skills and the improvement of language-based skills in students with reading disabilities. Scarce data and literature exist that effectively connect the two domains. Yet, there is some evidence that implementing NLB trainings has had transforming effects on language-based (LB) skills and effected broader benefits to students’ cognition. Findings show a lack of studies of NLB skills, study designs that ignore these skills and their developmental trajectories, and a mixed result of training effects. Suggestions are made for educators and researchers to further investigate potential effects of NLB training in reading challenged individuals within this framework.